Brazilian youths' attitudes towards contemporary social values - Abulhul, Zeinab (Technium Social Sciences Journal, 2020)
This study aims to compare the outcomes from the study conducted by dos Santos et al. (2012) to the results found by researcher on her investigation about the impact of setting a minimum wage policy on young Brazilians' attitudes toward contemporary social values, which the data was collected from quantitative world survey. The research used the following questions to examine Brazilian youths attituded towards contemporary social values; Is there a relationship between households' satisfaction with the financial situation and the current Brazilian youths’ attitudes toward contemporary social values? Is there a relationship between socio-economic and Brazilian youths’ conceptions of achievement and success? Is there a relationship between social class and Brazilian youths’ opinion toward parents using physical punishment to discipline their children? The researcher used the following methods to examine the differences between the study variables; descriptive statistical analysis to present key variables in the sample, along with correlation, t-tests and ANOVA to further examine the relationships between variables. The results showed there was no statistically significant relationship between satisfactions with household financial situation and attitudes about doing good in society (social values), there was not a statistically significant difference in the mean scores between attaining/not attaining a university education and attitudes about achievement and success, and there was not a statistically significant difference in means scores among the three social classes in attitudes about physically punishing children. By comparing the outcomes from the study conducted by dos Santos et al. (2012) to the results from my investigation, I found there was similarity of opinions between participants in which education has relationship to having better future and helping youth become more independent; however, there were differences in opinions about the justifiability for parents to use physical punishment to discipline their children..